1991
DOI: 10.1159/000138777
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Histamine on Human Placental Chorionic Veins: Interaction with Serotonin

Abstract: The vasomotor effects of histamine and its interaction with serotonin were studied in isolated human placental chorionic veins. Histamine induced concentration-dependent contractions with an EC50 of 8.7 ± 1.2 × 10–6 mol/l. The H1 antagonist, pyrilamine (10–9 to 10–7 mol/l), inhibited histamine-induced contractions, with a pA2 of 8.33 ± 0.32 at a slope of 0.635. Cimetidine (H2 antagonist) had no effect on histamine-induced contractions. Serotonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…H1R and H2R are distributed in the uterine tissue (6). H1R can stimulate the immune system to enhance immune response and inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H1R and H2R are distributed in the uterine tissue (6). H1R can stimulate the immune system to enhance immune response and inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine is responsible for biological functions, such as the expression of histamine receptors (mainly H1R, H2R, H3R, and H4R) relying on target cells (8,13). Among these receptors, H1R and H2R are expressed in endometrial cells and immune cells (6). Yamaki et al (25) suggested that histamine increases the expression of cell adhesion molecules in endothelial cells, such as ICAM-1, VCAM-1, and P-lectin, through H1R.…”
Section: Introductionmentioning
confidence: 99%
“…The important role of increased serotonin levels in pre-eclampsia has been documented [5,6]. In our earlier studies, we have shown that serotonin causes intense vasoconstriction in isolated human placental vessels [7], and that threshold concentrations of serotonin increase sensitivity to other vasocon-strictors [8,9]. Furthermore, the presence of a specific 5-HT 2 receptor has also been demonstrated in the umbilical and placental vessels [10,11].…”
Section: Introductionmentioning
confidence: 92%
“…Thus, the influence of vasodilator mechanisms obviously predominates during normal preg nancy. However, in various pathological states associated with pregnancy, changes in the balance of opposing vaso constrictor and vasodilator humoral autacoids may well make a significant contribution to the observed increased placental resistance to blood flow [2], Several substances that can affect vascular tone have been detected in the competitive inhibitor of the type 2 serotonin receptor, can control the hypertension of preeclampsia [8], In addition, serotonin has the ability to increase the contractions evoked by other agents in different vessels [9,10]. All these observations suggest that serotonin may play a role in the control of fetal vascular tone in the human placenta in normal and/or pathological conditions.…”
Section: Introductionmentioning
confidence: 99%